Is the short axis view of the fetal heart useful in improving the diagnostic accuracy of outlet ventricular septal defects?†. (5th January 2017) - Dall'Asta, Andrea; Cavalli, Claudio; Galli, Letizia; Volpe, Nicola; Weiss, Adi; Kaihura, Christine Tita; Agnetti, Aldo; Frusca, Tiziana; Ghi, Tullio
Abstract: Objectives: Outlet ventricular septal defects (VSDs) are usually suspected on the five‐chamber view of the fetal heart; however, postnatal confirmation occurs only in a small number of cases. The aim of this study was to evaluate if the systematic assessment of the short axis view may improve the prediction of prenatally detected outlet VSDs. Methods: Cases where isolated outlet VSD was suspected on the five‐chamber view were assessed by using the short axis scanning plane for confirmation of the defect. Postnatal assessment was performed within 2 weeks from birth at our Paediatric Cardiology Unit. Results: An outlet VSD was suspected at five‐chamber view in 23 fetuses. Postnatal confirmation of the VSD occurred in 14 cases where the defect was prenatally detected both on the five chamber and the short axis views. VSDs were not confirmed at postnatal assessment only in two cases where outlet VSD was suspected on both views, whereas all the seven cases with a suspected VSD on the five‐chamber view only turned out to be false positives. Conclusion: The short axis view of the fetal heart seems useful in confirming the presence of outlet VSDs. © 2016 John Wiley & Sons, Ltd. Abstract : WHAT'S ALREADY KNOWN ABOUT THIS TOPIC? Prenatal ultrasound has proven to yield a poor specificity in the diagnosis of outlet ventricular septal defects. Prenatal diagnosis of ventricular septal defects is usually based on abnormal findings on five‐chamber view. WHAT DOES THIS STUDY ADD? The short axis view of the fetal heart seems useful in improving the prediction of prenatally suspected outlet ventricular septal defects.